2019
DOI: 10.7150/ijbs.35347
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Origin of Claudin7 in Early Tumor Endosomes Affects Exosome Assembly

Abstract: Microvesicles are the body's most powerful intercellular communication system and cancer-initiating cell microvesicles (CIC-TEX) reprogram Non-CIC towards fortified malignancy. Claudin7, a CIC-biomarker in gastrointestinal tumors, is recovered in TEX. Recent evidence suggesting individual cells delivering distinct microvesicles became of particular interest for claudin7, which is part of tight junctions (TJ) and glycolipid-enriched membrane domains (GEM), GEM-located claudin7 is palmitoylated. This offered the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 73 publications
(111 reference statements)
0
7
0
Order By: Relevance
“…Chiba recruited exosomes from SW480 cells (GSE68979), and Ji et al distinguished three subtypes of EVs from the human LIM1863 cancer cell line [131]. Moreover, Sun and his group reported their results in HT-29 and SW-948 cells [134,135]. Some stem cell markers (CD44v6, Tspan8, CD151, and Claudin7) have been manipulated in exosome research.…”
Section: Available Omics Datasets Of Evs For Crcmentioning
confidence: 99%
“…Chiba recruited exosomes from SW480 cells (GSE68979), and Ji et al distinguished three subtypes of EVs from the human LIM1863 cancer cell line [131]. Moreover, Sun and his group reported their results in HT-29 and SW-948 cells [134,135]. Some stem cell markers (CD44v6, Tspan8, CD151, and Claudin7) have been manipulated in exosome research.…”
Section: Available Omics Datasets Of Evs For Crcmentioning
confidence: 99%
“…It has also been shown that Cld7 can be distributed beyond TJ sites. For instance, palmitoylated Cld7 (Palm-Cld7) is localized in glycolipid-enriched membrane microdomains (GEMM) [ 113 ]. Cld7 in tight junction (TJ-Cld7) is shown to regulate the entry of related proteins into PaCaExos and affect the function of exosomes derived from CICs (CIC-Exos) by modulating the composition of exosomal transporters and lipid metabolites, while Palm-Cld7-positive exosomes have the capability of regulating cell migration [ 113 ].…”
Section: Exosomes and Paca Metastasismentioning
confidence: 99%
“…For instance, palmitoylated Cld7 (Palm-Cld7) is localized in glycolipid-enriched membrane microdomains (GEMM) [ 113 ]. Cld7 in tight junction (TJ-Cld7) is shown to regulate the entry of related proteins into PaCaExos and affect the function of exosomes derived from CICs (CIC-Exos) by modulating the composition of exosomal transporters and lipid metabolites, while Palm-Cld7-positive exosomes have the capability of regulating cell migration [ 113 ]. Importantly, Kyuno and colleagues have found that murine pancreatic cancer initiating cells (PaCICs) can produce Cld7-positive exosomes which are capable of inducing re-programming of non-metastatic cancer cells to further increase their invasiveness [ 113 ].…”
Section: Exosomes and Paca Metastasismentioning
confidence: 99%
See 1 more Smart Citation
“…Intracellular vesicle traffic remains to be defined (378). Alternatively, Exo-recruitment during biogenesis is not excluded (390) and would be consistent with pronounced coimmunoprecipitation of cldn7 with Golgi-endoplasmic reticulum (ER) transporters (391).…”
Section: Claudin7 and Epcammentioning
confidence: 99%